2019
DOI: 10.1007/s11368-019-02430-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term carbon and nitrogen dynamics in soil, litterfall and canopy of a suburban native forest subjected to prescribed burning in subtropical Australia

Abstract: Purpose This study aimed to understand the mechanisms of the variations in carbon (C) and nitrogen (N) pools and examine the possibility of differentiating the burning effects from seasonal and pre-existed N limitations in a native suburban forest ecosystem influenced by prescribed burning in subtropical Australia. Materials and methods Soil and litterfall samples were collected from two study sites from 1 to 23 months since last burnt. Soil labile C and N pools, soil C and N isotopic compositions (δ 13 C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…A slight overall increase in N concentration in the needle fraction was detected in the burned plots in comparison with the non-burned plots; this was also reported by Tahmasbian et al (2019) for suburban eucalyptus stands. However, other authors reported that foliar N concentration was not affected by prescribed fire (Landsberg et al, 1984).…”
Section: Discussionsupporting
confidence: 81%
“…A slight overall increase in N concentration in the needle fraction was detected in the burned plots in comparison with the non-burned plots; this was also reported by Tahmasbian et al (2019) for suburban eucalyptus stands. However, other authors reported that foliar N concentration was not affected by prescribed fire (Landsberg et al, 1984).…”
Section: Discussionsupporting
confidence: 81%
“…Close proximity of shade trees to cocoa and coffee trees did not reduce nutrient concentrations in the topsoil for the cash crop trees (Figures 2 and 3), as soil TN and K concentrations at 0-10 cm depth in the cocoa-only or coffee-only positions were higher than minimum-required concentrations based on previous recommendations (Nelson et al, 2011;Sousa et al, 2018). The topsoil TN concentrations in this study were within the range reported in our previous study in a nearby cocoa-canarium plantation; however, soil K concentrations were lower than reported previously, that is, 360 mg/kg versus 496 mg/kg (Bai et al, 2022).…”
Section: Effects Of Shade Trees On Nutrient Concentrations In the Soi...mentioning
confidence: 57%
“…Canarium litter also tends to retain both N and K, whereas cocoa litter retains N but mineralises K, when canarium and cocoa litter are incubated for 12 months (Bai et al, 2022). The mineralised forms of N (e.g., NO 3 À -N) and K are highly leachable, and so asynchronised litter decomposition rates could be one of the mechanisms explaining why soil N and K were above minimum-required concentrations for cocoa and coffee based on previous recommendations (Nelson et al, 2011;Sousa et al, 2018). Additionally, site condition affects the litter residence time which, in turn, governs nutrient inputs from litter.…”
Section: Effects Of Shade Trees On Nutrient Concentrations In the Soi...mentioning
confidence: 94%
See 2 more Smart Citations